2018
DOI: 10.1177/1933719117749758
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Oxidative Responses in Pregnancies With Obesity and Periodontal Disease

Abstract: Obesity and periodontal disease could synergistically amplify the inflammatory and oxidative status, resulting in increased local and systemic biomarkers particularly when GDM is diagnosed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 58 publications
1
48
0
6
Order By: Relevance
“…Some previous studies have reported a positive association between excessive weight and periodontitis during pregnancy. Nonetheless, these studies used different methodologies for the classification of periodontitis and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have reported a positive association between excessive weight and periodontitis during pregnancy. Nonetheless, these studies used different methodologies for the classification of periodontitis and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that both obesity and pregnancy may negatively impact the periodontal condition, the periodontal response should be assessed in pregnant women with obesity during pregnancy. Reports have indicated the association between overweight/obese status and periodontitis during pregnancy [16][17][18][19][20][21] . However, due to the heterogeneity of definition of periodontitis and obesity in those studies, comparison between studies is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Zambon et al (35) documented that obesity amplify the inflammatory and oxidative status during pregnancy resulting in increased local and systemic biomarkers particularly when GDM is diagnosed. Also, Lindsay et al (36) reported a high rate of IR among pregnant women of moderately older age and high rate of obesity especially if diagnosed late in gestation.…”
Section: Discussion:-mentioning
confidence: 99%
“…Type 2 diabetes mellitus is considered an aggravating factor of periodontal disease and its incidence has been increasing due to several reasons, such as sedentary lifestyle, obesity, increased life expectancy, and higher survival of diabetic patients (ZAMBON et al, 2018, WOOTON, 2018. Thus, further studies are required to assess the correlation between both diseases.…”
Section: Introductionmentioning
confidence: 99%